2008
DOI: 10.1055/s-0028-1098728
|View full text |Cite
|
Sign up to set email alerts
|

Sexualität im Internet

Abstract: Übersicht: Mit "Internet-Sexualität" sind sämtliche sexualbezogenen Inhalte und Aktivitäten gemeint, die im Internet zu beobachten sind. Empirische Forschungsarbeiten zur Internet-Sexualität werden seit 1993 in stetig wachsender Zahl publiziert. Der vorliegende Beitrag fasst erstmals den aktuellen Forschungsstand in seiner thematischen Breite zusammen und behandelt sechs Bereiche der Online-Sexualität: Pornografie, Sexshops, Sexarbeit, Sexualaufklärung, Sexkontakte und sexuelle Subkulturen im Internet. Zentral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 85 publications
(96 reference statements)
0
3
0
5
Order By: Relevance
“…Their application in commercial sex has thus created a new niche in the market, with both benefits and drawbacks. On the one hand, some sex workers consider interactions via webcam more comfortable or safe than working on the street or in other face‐to‐face settings (Döring, ). A study by Cunningham and Kendall () showed that online sex workers took fewer risks than street‐based workers and differed generally in other behavioral and demographic factors, suggesting that the Internet may have contributed to change in this population group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their application in commercial sex has thus created a new niche in the market, with both benefits and drawbacks. On the one hand, some sex workers consider interactions via webcam more comfortable or safe than working on the street or in other face‐to‐face settings (Döring, ). A study by Cunningham and Kendall () showed that online sex workers took fewer risks than street‐based workers and differed generally in other behavioral and demographic factors, suggesting that the Internet may have contributed to change in this population group.…”
Section: Resultsmentioning
confidence: 99%
“…Online sexual activity (OSA) has been defined as any activity on the Internet involving sexuality aimed for instance at recreation, entertainment, education, or partner search (Cooper, Delmonico, Griffin‐Shelley, & Mathy, ). The Internet provides a framework for having new sexual experiences in a playful and safe way (Döring, ), and is usually easily accessible, affordable, and anonymous (the characterization of these features as the Triple‐A‐Engine (Cooper, Scherer, Boies, & Gordon, ) has meanwhile been expanded by Barak and Fisher () to a Penta‐A‐Engine, adding the components of acceptability and aloneness). Another influential factor for the expansion of OSA is the online disinhibition effect, with both its benign and problematic qualities, such as opening up about private matters or verbal aggression towards others, respectively (Suler, ).…”
Section: Introductionmentioning
confidence: 99%
“…(6) Niederlande, Peter und Valkenburg (2006-2008: In der ersten bzgl. Alter, Geschlecht und Bildung repräsentativen Studie dieser Arbeitsgruppe gaben von 745 Adoleszenten im Alter von 13-18 Jahren 71 % der Jungen und 40 % der Mädchen an, Pornografie im Internet während der letzten sechs Monate ausgesetzt gewesen zu sein; wiederum waren die täglichen Pornografie-Konsumenten ausschließlich Jungen (2-4 % bzgl.…”
Section: Quantitative Querschnittsstudienunclassified
“…Z Sexualforsch 2011; 24 Hill A untersucht, gleiches gilt für die Nutzung des Internet aus sexuellen Motiven heraus(Döring 2008;Hill et al 2007;Hill 2011). Dies hat möglicherweise mit ethischen Grundpositionen der Forscher zu tun bzw.…”
unclassified
“…Wenngleich die meisten Nutzer und Nutzerinnen von Cybersex ihren Konsum als Bereicherung ihres Alltags betrachten [4], gibt es auch Personen, die unter ihrem exzessiven Einleitung ▼ Das Internet bietet vielfältige Möglichkeiten für sexuelle Aktivitäten. Darunter fallen der Konsum von Internetpornografie in Bild-und Videoform, das Nutzen von Sexchats, Sex via Webcam, das Suchen und Finden anderer Personen für sexuelle Abenteuer, den Erhalt von Informationen über sexuelle Themen, das Finden von Kontakten für bezahlbare sexuelle Aktivitäten, das Kaufen von Sexprodukten und das Lesen pornografischer Literatur online [1]. Während einige Autoren den Begriff "Cybersex" recht weit fassen und im Wesentlichen die genannten Aktivitäten darunter subsumieren, verstehen andere unter Cybersex…”
unclassified